(untitled) (International Journal of Information Technology and Computer Engineering, 2024)
In order to assist customers in making informed decisions about items that would help them save money online, price comparison sites compare prices from various vendors. Customers, particularly those residing in urban areas, tend to have hectic schedules, thus they find it more convenient to purchase their necessities online. Plus, shoppers usually look for the best deal when they buy anything; using price comparison websites, they can easily get the best deal without leaving the comfort of their own home. They may easily get the best deals on the things they need by checking the price comparison website directly. Price4You is the site where consumers can locate the best discounts on various items. The top sales will be shown prominently. online crawlers and online scraping methods are used to get extensive information in order to find the greatest discounts from price comparison websites. In this approach, the paper hopes to provide a solution that will allow online shoppers to save time, money, and effort when purchasing things.